THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT ON IMPROVING THE QUALITY OF EDUCATION AT SMPN 4 LEUWILIANG - Syamsul Rizal Mz; Syafira Aulia (Program Studi Manajemen Pendidikan Islam, 2026)
The main focus of human resource management is to improve the quality of education. The lack of training in HRM is the driving force behind this research. This study aims to find out how human resource management affects improving the quality of education at SMPN 4 Leuwiliang. Twenty-two educators and other education personnel participated in this quantitative descriptive study. This study used a quantitative approach with a survey method and involved all educators and education personnel. Data were collected through questionnaires, documentation, and a literature study. Assumption testing, including normality, homogeneity, and heteroscedasticity, as well as descriptive statistics, validity, and reliability, were all part of the data analysis. Then the correlation coefficient test of SPSS 27 Windows version, the simple linear regression test, and the determination coefficient test were used to test the hypothesis. The results of this study show that 42.3% of human resource management plays an important role in improving the quality of education. The conclusion of this study is that HRM has a major influence on improving the quality of education at SMPN 4 Leuwiliang, which is in the medium category